Military Aspects of the Dispute Between Poland and Lithuania over the North-Eastern Borderlands (1919–1920): a Polish Perspective - Jabłonowski, Marek; Jakubowski, Wojciech (History / Istorija, 2022)
Abstract. In 1918, the Republic of Poland, recovering from a century and a half of servitude, was in conflict not only with the former partitioning powers, but also with new nation states that were forming on their ruins. Lithuanians, creating their own state, rejected the proposal to return to the idea of a Polish-Lithuanian union. They chose the road to state independence, although, to do so, they often had to seek agreements with Germany and Soviet Russia. With the use of Polish literature on the subject, the article outlines the military aspects of the dispute between Poland and Lithuania over the Vilnius and Suwałki regions in the period when the foundations of the independence of both countries were being shaped, focusing on the period 1919–1920. The source base for the study consists mainly of documents of military provenance.